Diseño y construcción de un tablero de control y mando de motores, con el sistema electromecánico y sistema digital (PLC). - Aguilera Díaz, Dany Alexander (2011)
In the present researching work is shown the design and construction of a switchboard to control engines with the electromechanical system and digital system (PLC), to the realization of practices where students of “Área de la Energía, las Industrias y los Recursos Naturales no Renovables” acquire and develop abilities and skills needed to perform without any difficulties in their professional field. It is within the parameters assimilated during the years of formation and learning in the career of Tecnología en Electricidad, besides the advice from a professional with wide experience regarding automatization. We consider that the present researching work has great importance because it will enable students from the career deepen a bit more in the field of automatization, therefore they could develop a great many of useful practices to learn how to assemble a system that lets controlling a process whichever it be and that may be present in their future professional lives. It is suggested to continue with the study and development of other general schemes of automatization to engines with the PLC LOGO SIEMENS, to obtain new designs appropriate to the industrial conditions of Loja and the southern region of the country.